Influência da fadiga muscular na assimetria da rigidez dos membros inferiores - Thamara Monteiro Vieria (2019)
This study aimed to verify the effect of muscular fatigue on the stiffness of the lower limbs. We also aimed to understand whether the effect of fatigue is similar between the two lower limbs using the changes (post – pre) in the knee joints’ stiffness after a fatigue protocol. Information on the changes in each knee joint stiffness after the fatigue protocol and their contribution to the changes in vertical stiffness is important for training load monitoring. Twenty-three male participated in this study. They performed a countermovement test on a force platform before and after the fatigue protocol. The fatigue protocol consisted of 100 countermovement jumps, performed as 5 bouts of 20 jumps with 30 seconds of passive recovery in-between. The decline of jump performance over the bouts suggested that participants were fatigued after the protocol. The knee joint stiffness (Kknee) was assessed due to the greater changes in the range of motion of the knee joint during the countermovement jump. We also assessed the vertical stiffness (Kvert), which refers to the changes in the height of the center of mass of each lower limb. We obtained the peak force from the ground reaction force recorded by the force platform during the CMJ. A kinematic analysis was used to calculate the angles of the knee joints. A two-way mixed ANOVA and the Bonferroni’s post hoc were used to compare the means. A linear regression was used to predict the asymmetry of Kvert (dependent variable) from Kknee data (independent variable). In all cases, statistical significance was set at 5%. Results showed a reduction of the Kknee after the fatigue protocol, as well as an absence of increase in the asymmetry of the Kknee. The asymmetry of the Kknee had a greater influence on the asymmetry of the Kvert in the pre-test (R2= 59%) compared with the post-test (R2= 24%). We can conclude that the fatigue protocol reduced the Kknee but did not change the its asymmetry. The explanation of the asymmetry of the Kvert based on the asymmetry of Kknee changes depending on the level of fatigue (pre vs. posttests).